Lost in translation: The fractured conversation about trade and food security - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2015)
There is a heated debate among policy makers, civil society, and analysts about the impact of trade and trade policies on food security. While there have been several empirical reviews on these issues the controversy has not abated. This paper surveys possible reasons why the polemic continues and why it may be difficult to settle it unequivocally. The reasons are related to the different notions of trade, food and nutrition security, the variety of possible indicators for those concepts, the multiplicity of channels through which trade and food and nutrition security notions interact, the diversity of analytical and quantitative approaches utilized, and differences in values and conceptual priors about the operation of the world economy. The paper concludes with some reflections about what can be reasonably said about the potential impacts of trade on food security.